Determinant Factors of Early Menarche among Primary School Girls - Firdawati Firdawati; Fadiyah Rahmatias; Abdiana Abdiana; Henni Fitria (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Early menarche, defined as the onset of menstruation before the age of twelve, has been linked to adverse physical and mental health outcomes and is a key predictor of rapid pubertal growth. Although data at the elementary school level in Indonesia remain limited, recent findings suggest a rising prevalence of early menarche in urban areas. This study provides local evidence from an urban school in Padang City, where early menarche appears to be increasing. This research examined associations between early menarche among elementary school girls in Public Elementary School (SDN) 03 Alai Timur, Padang City, and factors including nutritional status, maternal age at menarche, and exposure to mass media information technology. Statistical analyses were conducted using the Chi-square test and the Fisher Exact Test, with a significance level of p < 0.05. Results showed that three-quarters of the participants experienced early menarche. Overweight-obese nutritional status was significantly associated with higher rates of early menarche (95.2%; p=0.011), as was high exposure to mass media information technology (88.9%; p=0.020). Although not statistically significant (p=0.071), girls whose mothers had experienced early menarche also showed higher rates (90.0%). Overall, early menarche was strongly associated with nutritional status and media exposure, while maternal age at menarche demonstrated a non-significant intergenerational effect. The findings highlight the need for schools to implement programs that educate young girls on proper nutrition, responsible media consumption, and reproductive health from an early age. Keywords: Early Menarche, Elementary School Students, Nutritional Status, Maternal Menarche History, Mass Media Exposure.